The integration of dynamic value stream mapping and cost time profile method for optimizing offshore drilling logistic base operations - Kenedy, Martino Dedy; Widyadana, I Gede Agus (Indonesian Journal of Multidisciplinary Science, 2024)
The research aims to analyze the integration of Dynamic Value Stream Mapping (DVMM) and Cost Time Profile (CT-profile) method for optimizing offshore drilling logistic base operations. The novelty of the research is the implementation of DVMM and CT-profile that implemented in monitoring system INTACTS (Integrated Dynamic value stream mapping and Cost time profile for shore base operation) which is directly connected to shore base material movement recording system. Each successful lift performed in JIT mode will be recorded and its characteristics studied so that it can be applied to other material lifting operations. This research uses data on the lifting operation on July - December 2020. The new method is applied in a logistic system for drilling activity. The research shows that DVSM is suitable to be applied for logistics in off shore base problems since the job and situation are very dynamics.